2015
DOI: 10.1111/anae.13155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stroke volume variation‐directed fluid management on blood loss during living‐donor right hepatectomy: a randomised controlled study

Abstract: Summary Reducing blood loss is beneficial in living liver donor hepatectomy. Although it has been suggested that maintaining a low central venous pressure is important, it is known that low stroke volume variation may be associated with increased blood loss. Therefore, we compared the effect on blood loss of 40 patients randomly assigned to a high stroke volume variation group (maintaining 10–20% of stroke volume variation) vs 38 patients in a control group (maintaining < 10% stroke volume variation) during li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
1
23
1
Order By: Relevance
“…1). During the period of this study, 2 reports were presented regarding high SVV management during liver transection in livingdonor right hepatectomy set at 10%-20%, 19,20 but there has been no report of management with SVV as an indicator in conventional open-liver resection for liver diseases. In this study, to achieve the target SVV, we mainly addressed fluid restriction only.…”
Section: Discussionmentioning
confidence: 99%
“…1). During the period of this study, 2 reports were presented regarding high SVV management during liver transection in livingdonor right hepatectomy set at 10%-20%, 19,20 but there has been no report of management with SVV as an indicator in conventional open-liver resection for liver diseases. In this study, to achieve the target SVV, we mainly addressed fluid restriction only.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of SVV in guiding intraoperative fluid administration has been reported in many clinical contexts, such as in hepatic and neurosurgical surgeries. 10 , 22 , 23 Importantly, our group has previously suggested that maintaining a high SVV is a useful way to reduce blood loss during living donor right hepatectomy. 10 , 11 , 24 Additionally, a higher SVV value has been reported to correlate with a lower right ventricular end-diastolic volume index value in liver transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 22 , 23 Importantly, our group has previously suggested that maintaining a high SVV is a useful way to reduce blood loss during living donor right hepatectomy. 10 , 11 , 24 Additionally, a higher SVV value has been reported to correlate with a lower right ventricular end-diastolic volume index value in liver transplant recipients. 12 The maintenance of a high SVV appears to induce lower normal levels of intravascular volume and to thereby prevent vascular congestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first prospective report by Jones et al [15] stated that maintaining a low CVP is a widely used method to minimize intraoperative blood loss [16,17], CVP is believed to reflect the hepatic sinusoid pressure, rendering it an effective indicator for reducing hepatic parenchymal congestion, thus reducing blood loss and controlling hepatic venous hemorrhage [18], it is well known that a target CVP during hepatic resection is 5 mmHg or lower has shown significant reduction of bleeding, morbidity and mortality [16][17][18].…”
Section: Introductionmentioning
confidence: 99%